Development of Isohyet Map of Design Rainfall using Spatial Interpolation at Various Return Periods in Sadar Sub-Watershed - Donny Harisuseno; Jadfan Sidqi Fidari; Syifa Nissa Aulia (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2024)
The overflow of the Sadar River often causes flooding, which is detrimental to the community. Effective measures to address the flood problem require a good quality and quantity of rainfall data. This study aims to develop an isohyetal map of design rainfall for various return periods using the interpolation linear method. The design rainfall is computed using frequency analysis of Log Normal, Gumbel, and Log Person III distributions with return periods of 2, 5, 10, 25, 50, and 100 years. The isohyet map was produced using the Inverse Distance Weight (IDW) and spline interpolation methods. The map results are then evaluated against the design rainfall values obtained from the frequency analysis using the NSE and RSR parameters. The IDW and spline interpolation maps show an excellent level of fit. Furthermore, the isohyet map was compared with the design rainfall map issued by the Ministry of Public Works and Public Housing, which shows a level of fit of 49.693% for the IDW method and 33.194% for the spline method. The results confirmed that the IDW method is the most accurate to estimate isohyet map of design rainfall in the study area.